Differential effects of different antipsychotic drugs on cognitive function in patients with chronic schizophrenia. (17th September 2020) - Dong, Rui; Yuan, Lian; Yang, Yong; Du, Xiang‐Dong; Jia, Qiufang; Dillon, Brett A.; Yu, Liling; Zhang, Xiang Yang
Abstract: Background: Cognitive impairment is core feature of schizophrenia. The impact of antipsychotics on cognition remains controversial. This study aimed to examine the effects of long‐term use of different types of antipsychotics on cognitive impairment in schizophrenia patients. Methods: We used the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) to assess the cognition of three groups of schizophrenia patients (318 on clozapine, 125 on risperidone, and 166 on typical antipsychotic drugs) and 399 healthy controls, and used the Positive and Negative Syndrome Scale to assess schizophrenia symptoms of patients. Results: Patients taking typical antipsychotics scored higher on the immediate memory and delayed memory index than those taking clozapine or risperidone (all p < 0.01). Patients taking clozapine scored higher on the language subscale than those taking risperidone ( p < 0.05). Multiple regression analysis showed that the drug type was identified as an independent contributor to the immediate memory, language, and delayed memory index of RBANS (all p < 0.05). Conclusions: Patients taking typical antipsychotics have better memory than those taking clozapine or risperidone. Patients taking clozapine have better language function than those taking risperidone.